Peran Gender dalam Pengelolaan Budidaya Tanaman Padi Pada Gapoktan Sumber Rejeki Desa Kalanganyar Kecamatan Karanggeneng Kabupaten Lamongan Jawa Timur - PURNAMA, PUPUT DEWI; ASTITI, NI WAYAN SRI; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Gender Roles in the Management of Rice Cultivation, A Case Study on The Farmers’ Group of Sumber Rejeki at Kalanganyar Village, Karanggeneng Subdistrict, Lamongan Regency, East Java Most women act as housewives, in addition to being active in household activities, rural women are also participating in rice farming activities from land-processing to harvesting. The study aimed to determine the role of gender in rice farming seen from three aspects, namely activity profile, access profile, and control profile (decision making). The research method used is survey method with interview approach. Data analysis was conducted descriptivelywith qualitative and quantitative methods. The findings showed that the role of women and men is different in every farming activity. (A) The profile of activity in the outpouring of male labor is greater than that of women, the average outpouring of male domestic labor is 199.16 hours per cultivating season and women is 123.41 hours per season with an average land area of 6, 64 ares. (B) In the access profile, men have greater access of 78.06% while women of 21.94% ,. (C) The women's participation control profile is very low compared with men, it means that the pattern of decision making is dominated by men up to 96.08%. Based on the results of research, it can be suggested that women should play an active role in productive and non productive work. Men are advised also to assist in the housework to relieve women's work so that the housework is not neglected. It is also expected to involve women in the extension so that they can increase participation in their farming activities.